Asian FTAs: Trends and challenges - Masahiro Kawai; Ganeshan Wignaraja (Asian Development Bank Institute (ADBI), 2009)
Although a latecomer, economically important Asia has emerged at the forefront of global free trade agreement (FTA) activity. This has sparked concerns about the negative effects of Asian FTAs, including the noodle bowl problem. Amid slow progress in the World Trade Organization's (WTO) Doha negotiations and the global financial crisis, however, Asian regionalism seems to be here to stay and the focus for policymakers should be how best to minimize the costs of FTAs while maximizing their benefits. Adopting a pragmatic perspective, this paper examines key trends and challenges in Asian FTAs. It provides new evidence from firm surveys, analysis of specific agreements, and computable general equilibrium estimates. It makes a case for strengthening the support system for using FTAs, rationalizing rules of origin and upgrading their administration, ensuring better coverage of agricultural trade, forging comprehensive WTO-plus agreements, and encouraging a region-wide FTA. Political economy considerations suggest that a likely scenario is for FTA consolidation in Asia to be followed by connections with North America and Europe. In conclusion, a bottom-up approach to a Doha Round Agreement emerges from the analysis.
Keywords: F1; F15; O24; 330; Freihandelszone; Handelsregionalismus; Asien